A 3–dimensional broadcast protocol with optimised transmission efficiency in wireless networks. (29th March 2013) - Lai, Yung–Liang; Jiang, Jehn–Ruey
Broadcasting is an important operation in the wireless network to disseminate information throughout the entire network. Flooding is a simple mechanism to realise broadcasting, but it has high redundancy of retransmissions, leading to low transmission efficiency. In this paper, we propose a 3D broadcast protocol, called 3DOBP (3–Dimensional Optimised Broadcast Protocol), to achieve optimised transmission efficiency by partitioning the 3D space into multi–layer hexagonal prisms of a hexagon ring pattern in each layer. The transmission efficiency of the proposed protocol is 1/π, which is higher than those of polyhedron–filling broadcasting approaches using cubes, hexagon prisms, rhombic dodecahedrons, and truncated octahedrons.